Influence of Wheel Contour Design on Characteristics of Non-Shroud Turbine Stage - T. A. Nikolaeva (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper considers the possibility to reduce leakages through a radial stage clearance owing to profile grooves on a peripheral wheel ring.